Neuropeptides: Metabolism to Bioactive Fragments and the Pharmacology of Their Receptors. Issue 3 (3rd June 2014) - Hallberg, Mathias
Abstract The proteolytic processing of neuropeptides has an important regulatory function and the peptide fragments resulting from the enzymatic degradation often exert essential physiological roles. The proteolytic processing generates, not only biologically inactive fragments, but also bioactive fragments that modulate or even counteract the response of their parent peptides. Frequently, these peptide fragments interact with receptors that are not recognized by the parent peptides. This review discusses tachykinins, opioid peptides, angiotensins, bradykinins, and neuropeptide Y that are present in the central nervous system and their processing to bioactive degradation products. These well‐known neuropeptide systems have been selected since they provide illustrative examples that proteolytic degradation of parent peptides can lead to bioactive metabolites with different biological activities as compared to their parent peptides. For example, substance P, dynorphin A, angiotensin I and II, bradykinin, and neuropeptide Y are all degraded to bioactive fragments with pharmacological profiles that differ considerably from those of the parent peptides. The review discusses a selection of the large number of drug‐like molecules that act as agonists or antagonists at receptors of neuropeptides. It focuses in particular on the efforts to identify selective drug‐like agonists and antagonists mimicking the effects of the endogenous peptide fragments formed. As exemplified in this review, many common neuropeptides are degraded to a variety of smaller fragments but many of the fragments generated have not yet been examined in detail with regard to their potential biological activities. Since these bioactive fragments contain a small number of amino acid residues, they provide an ideal starting point for the development of drug‐like substances with ability to mimic the effects of the degradation products. Thus, these substances could provide a rich source of new pharmaceuticals. However, as discussed herein relatively few examples have so far been disclosed of successful attempts to create bioavailable, drug‐like agonists or antagonists, starting from the structure of endogenous peptide fragments and applying procedures relying on stepwise manipulations and simplifications of the peptide structures.